Grenada : 2009 Article IV Consultation, Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Modification of Performance Criterion, and Financing Assurances Review-Staff Report; Public Information Notice; and Press Release. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This 2009 Article IV Consultation highlights that economic activity in Grenada is slowing significantly, reflecting the drag of the global crisis on tourism receipts, foreign direct investment, and remittances. Commercial banks have remained resilient, but the intervention of the Trinidad and Tobago-based CL Financial Group has heightened financial uncertainty. All quantitative targets for end-June 2009 were met. Executive Directors have commended the Grenadian authorities for the satisfactory performance of their economic program under these highly challenging circumstances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet